Bone Outcome after Treatment of Infected Nonunion Femoral Shaft Fracture by Ilizarov Method (The Planet, 2024)
Introduction: This study addresses the challenging issue of infected nonunion femoral shaft fractures, a condition complicated by soft tissue and bone involvement, persistent multi-bacterial infection, limb length discrepancy, deformities, joint stiffness, and multiple draining sinuses. This study aimed to analyze the bone outcome of treatment of infected non-union femoral shaft fracture by the Ilizarov method. Methods and materials: This prospective observational study, conducted at the National Institute of Traumatology and Orthopedic Rehabilitation (NITOR) in Dhaka, Bangladesh, spanned from May 2018 to August 2020. The study included 20 patients selected through purposive sampling. Data analysis was performed using the SPSS version 22.0 computer software program. Result: The mean bone gap was 2.7±1.7 cm, with 60% having a gap of 0 to 2 cm and 40% more than 2 cm. Radiological union took an average of 7.85±2.1 months, with 50% achieving union within 4 to 7 months and 50% within 8 to 11 months. Regarding limb length discrepancy, 25% had none, and the mean discrepancy was 1.2±0.9 cm. According to the Association for the Study and Application of the Method of Ilizarov (ASAMI) criteria, 40% had excellent bone outcomes, 45% were good, and 15% were fair. Conclusion: This study concludes that the Ilizarov ring fixator offers a reliable and successful method not only for stabilization and satisfactory bone union but also for correcting length discrepancies and eradicating infection.
Keywords: Femur; Ilizarov method; Infected; Non-union; Limb length discrepancy